6-Substituted purines as ROCK inhibitors with anti-metastatic activity - Voller, Jiří; Zahajská, Lenka; Plíhalová, Lucie; Jeřábková, Jana; Burget, David; Pataki, Andreea Csilla; Kryštof, Vladimír; Zatloukal, Marek; Brábek, Jan; Rösel, Daniel; Mik, Václav; Tkáč, Martin; et al. (Bioorganic chemistry, 2019)
Rho-associated serine/threonine kinases (ROCKs) are principal regulators of the actin cytoskeleton that regulate the contractility, shape, motility, and invasion of cells. We explored the relationships between structure and anti-ROCK2 activity in a group of purine derivatives substituted at the C6 atom by piperidin-1-yl or azepan-1-yl groups. Structure-activity relationship (SAR) analyses suggested that anti-ROCK activity is retained, and may be further increased, by substitution of the parent compounds at the C2 atom or by expansion of the C6 side chain. These inhibitors of ROCK can reach effective concentrations within cells, as demonstrated by a decrease in phosphorylation of the ROCK target MLC, and by inhibition of the ROCK-dependent invasion of melanoma cells in the collagen matrix. Our study may be useful for further optimization of C6-substituted purine inhibitors of ROCKs and of other sensitive kinases identified by the screening of a broad panel of protein kinases.
Keywords: molekulární struktura; signální transdukce; proliferace buněk; Humans; lidé; kinázy asociované s rho; Molecular Structure; puriny; vztahy mezi strukturou a aktivitou; Structure-Activity Relationship; Cell Proliferation; inhibitory proteinkinas; Antineoplastic Agents; Purines; pohyb buněk; Cell Line, Tumor; nádorové buněčné linie; rho-Associated Kinases; Protein Kinase Inhibitors; Signal Transduction; protinádorové látky; Cell Movement